Dynamics of Madrasah Aliyah in Indonesia: Insights from Schools, Educators, and Student - Cecep Wahyudin; R. Siti Pupu Fauziah; Afmi Apriliani; Faisal Tri Ramdani; Irma Purnamasari; Agustina Multipurnomo; Herli Andani; Endang Sri Murni; Bayu Sang Aji Pangestu (Jurnal Pendidikan Islam, 2024)
The growth and development of Islamic religious education are critical for strengthening educational quality in Indonesia. This study aims to analyze the growth dynamics of Islamic education through the increase in the number of schools, teachers, and madrasah aliyah students, providing insights for educational improvement. Using a descriptive approach, data were collected through Google Scholar using Publish or Perish software, covering 947 articles from 2018 to 2023, supplemented by secondary data via literature reviews. Data analysis utilized Microsoft Excel and VOSviewer software, with confirmability testing ensuring data validity. Findings indicate a steady increase in madrasah aliyah schools, with an additional 311 schools in 2022 and 372 in 2023. Teacher numbers also grew significantly, with an increase of 3,747 teachers in 2022 and 18,573 in 2023. Despite a decline in student numbers by 17,259 in 2022, student enrollment rebounded with an increase of 40,408 in 2023. This dynamic growth in schools and teachers reflects a rising demand for educational resources, driven by higher enrollment opportunities. The study suggests that harnessing Indonesia’s demographic bonus through targeted strategies could optimize educational outcomes, supporting the vision of "Indonesia Emas"